Uso de aveia branca em substituição ao milho nas características pós-abate de bovinos confinados sem volumoso - Machado, Diego Soares (2018)
The objective of this study was to evaluate the replacement of corn by white oat, in a non-roughage diet, on post-slaughter characteristics of non-castrated male bovines. Forty-five Charolais x Nellore crossbred animals, with initial age and weight of 18 months and 270.92 kg, respectively, were used. The experimental design was completely randomized. The steers were randomly distributed according to the level of replacement of the corn grain by white oat grain, being: 0; 25; 50; 75 and 100%. The diets were composed of 85% grain + 15% mineral-protein-vitamin nucleus. The hot and cold carcass yields presented quadratic behavior, with the inclusion of white oat grain as a substitute for corn grain. However, there was no influence of the diets on the other quantitative characteristics of the carcass. The non-carcass components were evaluated for their relative participation in empty body weight. The inclusion of white oat grain promoted a linear reduction in lung, heart, sum of internal organs, blood, rumen-reticulum and sum of cardiac, renal and pelvic fat. In contrast, omasum and abomasum weights presented a linear increase with the substitution of corn grain for white oat grain. Replacement of corn with white oats linearly reduced the coloring values (a *, b * and L *) of subcutaneous fat. There was a quadratic effect on the shear force and the thawing loss, with maximum points, for both characteristics between 29 and 34% of white oats, respectively. Among the sensorial characteristics, the palatability presented a quadratic adjustment, in which the minimum point was 52.22% of white oat. The lauric acid (C12: 0) presented quadratic behavior. The increase in white oat levels in the diet linearly reduced the participation of C18:1 trans- 10 + C18:1 trans- 11 fatty acids and linearly increased the participation of di-homo-γ-linolenic (C20: 3 n-6). The total saturated (45.73%) monounsaturated (45.83%) and polyunsaturated (8.03%) fatty acids, as well as the polyunsaturated/saturated ratio and the atherogenicity and thrombogenicity index were similar between the diets. The inclusion of white oat as a substitute for corn in a non roughage diet for cattle reduces the relative participation of vital organs, blood and visceral fat. The greater the inclusion of white oats in the diet, in substitution to corn, the lower the yellow intensity of the subcutaneous fat will become. The mixture of white oats and corn, between 29 and 34%, tends to increase the loss of liquids in thawing, making the meat slightly less tender and less palatable. The replacement of corn grain by white oat grain in non-roughage diet for cattle allows the obtainment of meat with a very similar lipid profile.